NUSANTARA ARTWORK AND ITS APPLICATIONS: A REVIEW OF TRADITIONAL ART PRACTICES AND CONTEMPORARY INNOVATIONS - Ramadhani, Dhika; Handriyotopo (Arty: Jurnal Seni Rupa, 2025)
Indonesian art has a rich and varied heritage, but in the current modern era, traditional art faces challenges to maintain its relevance. In the midst of the dynamics of social, economic and cultural change, artists and practitioners or art enthusiasts are starting to look for new ways to update things so that they become better or function optimally again and apply traditional arts in today's context. This study explores how traditional arts such as shadow puppetry, batik, masks, and other traditional performing arts are adapted, updated, and applied in various contemporary contexts. Through observations with artists, field research, and literature analysis, researchers identified various strategies and approaches used by artists in facing these challenges. This research aims to conduct a review of traditional Indonesian art practices and contemporary innovations that have emerged in their application today. The method used is descriptive qualitative and the study results show that there are various ways in which traditional art in the archipelago is revived, one of which is through interdisciplinary collaboration, integration of modern technology, educational and participatory approaches, as well as an emphasis on local values ​​and sustainability. The conclusion of this study is that Indonesian art remains a rich and relevant source of inspiration in facing challenges and opportunities in the world of contemporary art. This study makes an important contribution to understanding the application of traditional art in the archipelago to contemporary innovation.